EXPLORING THE KEY FEATURES OF FOUR LEARNING STYLES: A GUIDE TO PERSONALIZED EDUCATION - Axtamova, F.U; Yarqulova , D.M (Innovative Development in Educational Activities, 2023)
In the field of education, understanding diverse learning styles has become essential for creating effective learning environments. People have unique preferences, strengths, and ways of processing information. By recognizing and accommodating these differences, educators can maximize student engagement and learning outcomes. This article delves into the distinct features of four prominent learning styles: visual, auditory, reading/writing, and kinesthetic. Understanding these styles helps educators tailor their teaching strategies to meet the diverse needs of learners.